Critical reading and engagement matters: Integrating the flipped 5E inquiry instruction with Socratic seminars - Raweewat Sripradith; Supakorn Phoocharoensil (Universitas Syiah Kuala, 2025)
Despite the breadth of research on EFL reading comprehension, limited attention has been given to teacher support for critical reading and learner engagement in the Thai higher education context. This study applied Barrettes taxonomy as its analytical framework to explore whether tertiary students critical reading and engagement can be enhanced through an innovative blend of 5E inquiry-based instruction and Socratic seminars in a flipped classroom. The research employed a quasi-experimental one-group pretest-post-test design, focusing on 33 second-year English students, whose placement test results identified them as having low critical reading skills. The instruments used included 12-week lesson plans, critical reading pre- and post-tests, and self-reflective questionnaires. The findings demonstrated significant improvements in the participants critical reading comprehension, achieving a p-value of 0.001 at the 0.05 significance level (t = 8.586). During the reading activities, the students exhibited a moderate level of engagement in both the affective domain (M = 3.85, SD = 0.716) and the cognitive domain (M = 3.71, SD = 0.773. In addition, they demonstrated a high level of engagement in the behavioural domain (M = 4.35, SD = 0.651). These results contribute to the academic discourse concerning effective English teaching methodologies and offer practical implications for related EFL contexts. The study concludes with a discussion of its limitations and recommendations for future research, emphasizing the need for broader application and validation of these instructional strategies across diverse EFL learning environments.